The Deep Archaeal Roots of Eukaryotes - Yutin, Natalya (Oxford University Press, 2008)
The set of conserved eukaryotic protein-coding genes includes distinct subsets one of which appears to be most closely related to and, by inference, derived from archaea, whereas another one appears to be of bacterial, possibly, endosymbiotic origin. The “archaeal” genes of eukaryotes, primarily, encode components of information-processing systems, whereas the “bacterial” genes are predominantly operational. The precise nature of the archaeo–eukaryotic relationship remains uncertain, and it has been variously argued that eukaryotic informational genes evolved from the homologous genes of Euryarchaeota or Crenarchaeota (the major branches of extant archaea) or that the origin of eukaryotes lies outside the known diversity of archaea. We describe a comprehensive set of 355 eukaryotic genes of apparent archaeal origin identified through ortholog detection and phylogenetic analysis. Phylogenetic hypothesis testing using constrained trees, combined with a systematic search for shared derived characters in the form of homologous inserts in conserved proteins, indicate that, for the majority of these genes, the preferred tree topology is one with the eukaryotic branch placed outside the extant diversity of archaea although small subsets of genes show crenarchaeal and euryarchaeal affinities. Thus, the archaeal genes in eukaryotes appear to descend from a distinct, ancient, and otherwise uncharacterized archaeal lineage that acquired some euryarchaeal and crenarchaeal genes via early horizontal gene transfer.